2002
DOI: 10.1179/135100002125000758
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of oxidative stress in stroke-prone spontaneously hypertensive rat brain usingin vivoelectron spin resonance spectroscopy

Abstract: A number of researchers have reported that free radicals generated in the brain are involved in various brain dysfunctions, including ischemia-reperfusion injury, brain tumors, and neurodegenerative diseases. It has been reported that the spin probe MC-PROXYL can penetrate the blood-brain barrier and can be useful for evaluating oxidative stress in the brain. Preliminary comparisons were made by ESR imaging of the heads of live mice and isolated rat brains using the spin probe MC-PROXYL and the blood-brain-bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 14 publications
5
53
0
Order By: Relevance
“…1-3). We previously confirmed that the decay rate of MC-PROXYL in the isolated brains of SHRSP, a hypertensive reference strain (38) in which cerebral ischemia-reperfusion is known to occur due to oxidative stress (39,40), was also significantly faster than in the brain of WKY (29). Thus, the present study demonstrated a difference in the degree of oxidative stress between SHR and SHRSP brains.…”
Section: Fig 1 Two-dimensional Esr Projection Images (Y-z Plane) Ofsupporting
confidence: 72%
See 4 more Smart Citations
“…1-3). We previously confirmed that the decay rate of MC-PROXYL in the isolated brains of SHRSP, a hypertensive reference strain (38) in which cerebral ischemia-reperfusion is known to occur due to oxidative stress (39,40), was also significantly faster than in the brain of WKY (29). Thus, the present study demonstrated a difference in the degree of oxidative stress between SHR and SHRSP brains.…”
Section: Fig 1 Two-dimensional Esr Projection Images (Y-z Plane) Ofsupporting
confidence: 72%
“…ESR imaging is particularly useful for determining the in vivo spatial distribution of free radicals in animals. It has been suggested that MC-PROXYL is a suitable spin probe for the study of free radical reactions in the brain by in vivo ESR detection (23,29,30,33,34). Our data show that MC-PROXYL, but not carbamoyl-PROXYL, is well distributed in the brain and that the ESR signal decays in a time-dependent fashion.…”
Section: Fig 1 Two-dimensional Esr Projection Images (Y-z Plane) Ofsupporting
confidence: 49%
See 3 more Smart Citations